Experimental study of reinforced concrete columns concealing rain water pipe - Bakhteri, Jahangir; Syed Ariffin, Syed Ahmad Iskandar (Penerbit UTM Press, 2005)
An experimental study has been carried out to investigate the effect of concealing rain water pipes inside reinforced concrete columns in multistorey buildings. Fourteen columns in seven sets, having different sizes and reinforcement, with a PVC drain pipe positioned at the centre of crosssection of each one of them have been tested. An approximate method of columns’ alignment has also been developed and the alignment of the constructed columns has been carried out before their testing. The ultimate strength of the columns obtained from the present investigation have been compared with the design strengths recommended by the British code of practice (BS 8110) and the American code of practice (ACI). The columns showed significant reduction in their load carrying capacities and the safety factors obtained were much less than the nominal value usually recommended by various codes of practice.